Neurodegenerative Disorders with Hair Abnormalities: An Emergency Room Consultation for Dermatologists - Inamadar, Arun C (Medknow Publications, 2009)
Menke′s syndrome and Elejalde disease are the two neurodegenerative disorders of dermatological interest. These patients present with characteristic hair changes which may be of diagnostic value in resource-poor setup where facilities for specific genetic analysis are not available. Simple light microscopic examination of hair may be a helpful diagnostic tool to pick up such cases.